Disruption of the inositol phosphorylceramide synthase gene affects Trypanosoma cruzi differentiation and infection capacity. - Nailma S A Dos Santos; Carlos F Estevez-Castro; Juan P Macedo; Daniela F Chame; Thiago Castro-Gomes; Mariana Santos-Cardoso; Gabriela A Burle-Caldas; Courtney N Covington; Patrick G Steel; Terry K Smith; Paul W Denny; Santuza M R Teixeira (PLoS Neglected Tropical Diseases)
Sphingolipids (SLs) are essential components of all eukaryotic cellular membranes. In fungi, plants and many protozoa, the primary SL is inositol-phosphorylceramide (IPC). Trypanosoma cruzi is a protozoan parasite that causes Chagas disease (CD), a chronic illness for which no vaccines or effective treatments are available. IPC synthase (IPCS) has been considered an ideal target enzyme for drug development because phosphoinositol-containing SL is absent in mammalian cells and the enzyme activity has been described in all parasite forms of T. cruzi. Furthermore, IPCS is an integral membrane protein conserved amongst other kinetoplastids, including Leishmania major, for which specific inhibitors have been identified. Using a CRISPR-Cas9 protocol, we generated T. cruzi knockout (KO) mutants in which both alleles of the IPCS gene were disrupted. We demonstrated that the lack of IPCS activity does not affect epimastigote proliferation or its susceptibility to compounds that have been identified as inhibitors of the L. major IPCS. However, disruption of the T. cruzi IPCS gene negatively affected epimastigote differentiation into metacyclic trypomastigotes as well as proliferation of intracellular amastigotes and differentiation of amastigotes into tissue culture-derived trypomastigotes. In accordance with previous studies suggesting that IPC is a membrane component essential for parasite survival in the mammalian host, we showed that T. cruzi IPCS null mutants are unable to establish an infection in vivo, even in immune deficient mice.